A prospective 5-year follow-up study after limited resection for lung cancer with ground-glass opacity. (9th December 2017) - Sagawa, Motoyasu; Oizumi, Hiroyuki; Suzuki, Hiroyuki; Uramoto, Hidetaka; Usuda, Katsuo; Sakurada, Akira; Chida, Masayuki; Shiono, Satoshi; Abe, Jiro; Hasumi, Tohru; Sato, Masami; Sato, Nobuyuki; et al.
Abstract: OBJECTIVES: The incidence of small-sized pulmonary adenocarcinomas with ground-glass opacity (GGO) has recently increased, with excellent postoperative prognosis. The limited resection of such cancers has been deemed to be acceptable based on retrospective studies. We conducted a prospective multi-institutional study evaluating the validity of limited resection for small-sized pulmonary adenocarcinoma with GGO. METHODS: The inclusion criteria were 25–80 years of age, no prior treatment, a maximum tumour diameter of 8–20 mm, a GGO ratio of ≥ 80%, clinical T1N0M0, lower 18 F-fluorodeoxyglucose accumulation than the mediastinum, resectable by sublobar resection, pulmonary lobectomy tolerable and an intraoperative pathological diagnosis of bronchiloalveolar carcinoma. Wedge resection was preferred, but segmentectomy was permitted. Disease-specific survival and overall survival were analysed. RESULTS: From November 2006 to April 2012, 73 patients were enrolled from 13 institutions. One patient was ineligible, and the remaining 72 patients were preregistered. The tumours of 3 and 14 patients were intraoperatively diagnosed as benign lesions and adenocarcinomas with mixed subtype, respectively. Intraoperative cytological/histological examination of surgical margin was not performed in 2 patients, and the remaining 53 patients were ultimately eligible for this study. The mean tumour size was 14.0 mm and the mean GGO ratio was 95.9%. Thirty-nine and 14 patients underwent wedge resection and segmentectomy, respectively. Although all tumours were intraoperatively diagnosed as bronchioloalveolar carcinomas, 6 were ultimately diagnosed as adenocarcinoma with a mixed subtype. No completion lobectomy was performed. As of 1 May 2017, no recurrence of the original lung cancer was observed during 60.0–126.3 months after surgery. Two patients died from other diseases. The 5-year disease-specific and overall survival rates were 100% and 98.1%, respectively. The reduction in the pulmonary function after limited resection was minimal. CONCLUSIONS: With these criteria, limited resection was performed safely without any recurrence, and the postoperative pulmonary function was well preserved. The outcomes of limited resection for small-sized lung cancer with GGOs that met the criteria of this study were satisfactory.